Effects of time of grape pomace fermentation and distillation cuts on the chemical composition of grape marcs - Silva, M. Luz (1999)
The effects of fermentation time and distillation cuts on the composition of distillates in terms of ethanal, 1,1-diethoxyethane, methanol, 1-butanol, 2-butanol, 1-propanol, 2-methyl-1-propanol, 2-methyl-1-butanol, 3-methyl-1-butanol, ethyl acetate, ethyl 2-hydroxypropanoate, 3-methylbutyl acetate, hexyl acetate, 2-phenylethyl acetate, hexanol, trans-2-hexenol, trans-3-hexenol, cis-3-hexenol, 2-phenylethanol, ethyl butyrate, ethyl hexanoate, ethyl octanoate, ethyl decanoate, ethyl dodecanoate, 2-methylpropanoic acid, 3-methylbutanoic acid, hexanoic acid, octanoic acid, decanoic acid, and dodecanoic acid were assessed through data generated according to a factorial design using analysis of variance and principal component analysis. Four times of storage of pomace obtained following winemaking of two grape varieties of white Verde wine (Alvarinho and Loureiro) and three distillation cuts were considered; volatile compounds in the 24 samples generated were analyzed directly, and indirectly after extraction and concentration, by capillary gas chromatography. The results generated have suggested clear differences (P<0.05) between distillate cuts obtained throughout fermentation times for each grape variety. The major differences between the different distillate fractions analyzed were accounted for by the contents of diethyl butanoate, ethyl 2-hydroxypropanoate, and the sum of 3-methylbutanoic and 2-methylpropanoic acids for Loureiro, whereas the main differences were accounted for by the contents of diethyl butanoate and the sum of the carboxylic acids for Alvarinho.